2017
DOI: 10.1371/journal.pone.0188740
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel in a combined therapy with anticancer drugs—effect on tumor growth, metastasis, and treatment toxicity: Studies in animal models

Abstract: Clopidogrel, a thienopyridine derivative with antiplatelet activity, is widely prescribed for patients with cardiovascular diseases. In addition to antiplatelet activity, antiplatelet agents possess anticancer and antimetastatic properties. Contrary to this, results of some studies have suggested that the use of clopidogrel and other thienopyridines accelerates the progression of breast, colorectal, and prostate cancer. Therefore, in this study, we aimed to evaluate the efficacy of clopidogrel and various anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 61 publications
2
16
1
1
Order By: Relevance
“…The role of platelets in reducing cell death and enabling metastasis was also shown by activating YAP1 signaling in ovarian cancer ( 27 ). Similarly, many other reports show an active involvement of platelets in tumorigenesis and metastasis ( 28 32 ).…”
Section: Introductionsupporting
confidence: 70%
“…The role of platelets in reducing cell death and enabling metastasis was also shown by activating YAP1 signaling in ovarian cancer ( 27 ). Similarly, many other reports show an active involvement of platelets in tumorigenesis and metastasis ( 28 32 ).…”
Section: Introductionsupporting
confidence: 70%
“…Measurement of fluorescence of lungs dissected during autopsy was performed using the In Vivo MS FX Pro system with coregistration of fluorescence and X-ray. The obtained fluorescence images were analyzed using the Carestream MI SE software based on analyzed regions as described previously [56].…”
Section: Lung Fluorescence Measurementmentioning
confidence: 99%
“…Some studies performed on cancer mouse models have demonstrated that the use P2Y12 inhibitors, such as ticagrelor or clopidogrel, reduced tumor growth and metastasis in vivo [ 159 , 160 ]. The use of clopidogrel in combination with chemotherapeutic drugs enhanced vascular permeability and drug delivery [ 161 ]. Other studies, however, showed no effect of clopidogrel alone on the tumor growth of three cancer types, including breast, colorectal and prostate cancer, or, even worse, a pro-tumoral effect of prasugrel [ 161 , 162 ].…”
Section: Effects Of Cancer On Platelets and Mechanisms Involved Inmentioning
confidence: 99%
“…The use of clopidogrel in combination with chemotherapeutic drugs enhanced vascular permeability and drug delivery [ 161 ]. Other studies, however, showed no effect of clopidogrel alone on the tumor growth of three cancer types, including breast, colorectal and prostate cancer, or, even worse, a pro-tumoral effect of prasugrel [ 161 , 162 ]. Altogether the results observed may depend on the model studied and the design of the study.…”
Section: Effects Of Cancer On Platelets and Mechanisms Involved Inmentioning
confidence: 99%